Influence of codium tomentosum extract in the properties of alginate and chitosan edible films - Augusto, A (2018)
The growing search for natural alternatives to synthetic food packaging materials and additives has increased, and seaweed extracts' bioactivity has made them suitable candidates for incorporation in novel edible films. This study aims to investigate the effect of Codium tomentosum seaweed extract (SE) incorporation in alginate and chitosan edible films. Alginate- and chitosan-based films with and without the incorporation of 0.5% SE were characterized according to their physical, optical, mechanical, and thermal properties. Seaweed extract incorporation in chitosan films resulted in an increase of film solubility (50%), elasticity (18%), and decrease of puncture strength (27%) and energy at break (39%). In alginate films, the extract incorporation significantly decreased film solubility (6%), water vapour permeability (46%), and elasticity (24%), and had no effect on thermal properties. Depending on the type of application, the addition of SE in edible films can bring advantages for food conservation.